2018
DOI: 10.1093/cid/ciy1073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Malaria in the First Trimester of Pregnancy on Poor Maternal and Birth Outcomes in Benin

Abstract: Background In sub-Saharan Africa, malaria in the first half of pregnancy is harmful for both the mother and her fetus. However, malaria in the first trimester of pregnancy, when women are usually not protected against malaria, has been little investigated. For the first time, we assessed the effects of malaria in the first trimester on maternal and birth outcomes using a preconceptional study design. Methods From June 2014 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
1
17
1
3
Order By: Relevance
“…Our findings that sub-microscopic placental malaria was associated with a reduced risk of SGA birth was similar to results from a study done in Benin [37] despite differences in diagnostic methods and timing. The potential mechanism for this finding is unknown, but we speculate that it may involve the acquisition of antibodies in the placenta that inhibited the binding of P. falciparum-infected erythrocytes to the placental receptor chondroitin sulfate A (CSA) [38].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings that sub-microscopic placental malaria was associated with a reduced risk of SGA birth was similar to results from a study done in Benin [37] despite differences in diagnostic methods and timing. The potential mechanism for this finding is unknown, but we speculate that it may involve the acquisition of antibodies in the placenta that inhibited the binding of P. falciparum-infected erythrocytes to the placental receptor chondroitin sulfate A (CSA) [38].…”
Section: Discussionsupporting
confidence: 89%
“…As malaria is a cause of anemia, having several episodes increases the risk of anemia with its perinatal complications. Some researchers found that women who had malaria in the first trimester were more at risk of anemia in the third trimester 17 …”
Section: Discussionmentioning
confidence: 99%
“…Besides, the administration of IPTp-SP is only recommended from the second trimester onwards. The accurate identification and treatment of women with sub-microscopic infections in the first trimester of pregnancy may be of high clinical relevance considering the high prevalence and significant deleterious effects of these early infections [7][8][9].…”
mentioning
confidence: 99%